Heterogeneous price dynamics in US regional electricity markets - Dias, J. G. (2015)
The U.S. electricity wholesale market is organized in several deregulated regional markets. This paper compares price dynamics of electricity in the U.S. wholesale markets and shows that electricity prices from the West and East coasts have different regime dynamics. Our methodology suggests that electricity prices are better parameterized by four regimes with different levels of volatility. Additionally, West and East coast markets differ in the time spent in each regime. The extremely high volatility regime describes West coast prices during the California electricity crisis, but East coast prices are also frequent in that regime. We find evidence of synchronization of price dynamics in the mean-reverting and highest volatility regimes, i.e., prices from the East and West coasts tend to be in the same regimes at the same time.